PERANCANGAN MODEL PERAMALAN UNTUK DISTRIBUSI SEMEN DI PT INDOCEMENT TUNGGAL PRAKARSA TBK. UNIT CIREBON DENGAN MENGGUNAKAN AUTOML - Pratama Putra, Ryan
PT Indocement Tunggal Prakarsa Tbk. is one of the companies that produces cement in Indonesia. This company was founded in 1975 in the Citeureup area, Bogor, West Java. This company has factory branches in Palimanan, Cirebon, West Java; Tarjun, Kotabaru, South Kalimantan; and Tulisharjo, Grobogan, Central Java. PT Indocement Tunggal Prakarsa Tbk in the Cirebon area has a Shipping Department which is tasked with distributing cement throughout Indonesia. Therefore, PT Indocement Tunggal Prakarsa Tbk in the Cirebon area needs a forecasting model to be able to tell the amount of cement that will be distributed in the future. The design of the forecasting model uses historical data on cement distribution from January 2022 to March 2024. This design was carried out using Python programming with the Auto Machine Learning (AutoML) method. Later, from AutoML the best model can be obtained from the various models tested. In this research, the model chosen is Extremely Randomized Trees (XRT) which comes from H2O, a type of AutoML. This model was chosen because it has the best performance based on measuring error values such as Mean Absolute Deviation (MAD), Mean Squared Error (MSE), Root Mean Squared Error (RMSE), and Mean Absolute Percentage Error (MAPE). This forecasting model can be used to estimate the amount of cement distribution (in tonnes) for 12 months (a year) from April 2024 to March 2025. The amount of cement distribution is used to estimate the total vehicles needed for a year along with operational costs for cement distribution from April 2024 to 2024. March 2025. The estimated total vehicles needed for a year are 31.520 vehicles, with estimated cement distribution operational costs of IDR 71.632.436.000. This estimate is much smaller than the actual total vehicles for a year of 33.900 vehicles, with actual cement distribution operational costs of IDR 77.378.553.000.